Overexpression of HSP70 in mice with mutant FUS protein is accompanied by a mitigated neurodegeneration in limbic system - G. A. Piavchenko; K. S. Pokidova; E. A. Kuzmin; A. A. Venediktov; S. L. Kuznetsov (Сеченовский вестник)
Aim. To study morphological and developmental changes in the structure of mice’s limbic system, which overexpress 70 kDa heat shock proteins (HSP70) and co-express mutant fused-in-sarcoma (FUS) protein with amyotrophic lateral sclerosis (ALS).Materials and methods. The study was based on mice (n = 36; six for each group) of six lines either without FUS mislocalization: C57Bl/6 (wild-type); extracellular (HSP70out) or intracellular (HSP70in) overexpression of HSP70 family 1A protein; or with FUS mislocalization: transgenic mice with ALS-FUS (FUS[1-359]); and double transgenic animals (FUS[1-359]/HSP70out and FUS[1-359]/HSP70in). All FUS expressing mice were symptomatic with myasthenia up to limb paralysis in some animals. When the mice were 20 weeks old, they were killed by staining histological slides of their brain using hematoxylin and eosin, toluidine blue by Nissl, immunofluorescent antibodies for the neuronal nuclear marker (NeuN) of the caudoputamen, septal nuclei, and hippocampus, as well as glial fibrillar acid protein (GFAP), S100β protein, and synaptophysin for the hippocampus. The number of neurons and the number of cells with a positive reaction to antibodies were counted. The statistical processing included ANOVA and were compared with the results from the Tukey test for.Results. Statistically significant differences were observed for the FUS-expressing groups compared to FUS-negative groups: (1) a reduction in the number of neurons and NeuN+-cells in the caudoputamen and amygdala, especially for FUS[1-359]/HSP70out group; (2) an increase in the number of hyperchromic neurons in the subiculum, cornu Ammonis (CA1), and dentate gyrus, with a significantly greater increase for FUS[1-359] and FUS[1-359]/HSP70out groups compared to FUS[1-359]/HSP70in group; (3) an increase in the number of GFAP+and S100β+-cells in the hippocampus, with the most pronounced change for the FUS[1-359] and FUS[1-359]/HSP70out groups compared to с FUS[1-359]/HSP70in group.Conclusion. An overexpression of HSP70 family 1A protein and co-expression of mutant FUS protein in the cytoplasm is accompanied by mitigated neurodegeneration in the structure of the limbic system compared with the expression of mutant FUS protein alone.